Analysis of supplemental wildlife feeding in Mississippi and environmental gastrointestinal parasite load - Huang, Miranda H. J.; Demarais, Steve; Brookshire, W. Cooper; Strickland, Bronson K. (Frontiers in Veterinary Science, 2022)
Wildlife species are host to a variety of gastrointestinal parasites (GIPs). Artificially concentrating animals may increase the risk of disease spread due to increased GIP load and associated environmental load. Supplemental feeding of deer is common among hunters and known to concentrate animals, but there is limited knowledge of how it affects GIP environmental load. GIP load was compared between ecologically-equivalent pairs of sites in Mississippi with and without year-round supplemental feeding (average distance between pairs= 147 m). During May-August in 2019 and 2020, feces from white-tailed deer and raccoons were collected and examined for the presence of nematodes, coccidia, Giardia spp., Cryptosporidium spp., and Baylisascaris procyonis. On average, fed sites had 8 more deer (241% increase) and 2 more raccoon fecal piles (540% increase) than unfed sites. Average parasite loads for individual fecal samples did not differ between fed and unfed sites, but the greater number of deer and raccoon fecal piles at fed sites (p<0.0001) produced 231% and 308% greater environmental loads of nematodes and coccidia, respectively. Spin feeders, the only feeder type that distributed feed on the ground, had 326% more coccidia in feces on average compared to other feeder types (p<0.03). These results show that supplemental feeding of white-tailed deer, especially with spin feeders, increases environmental loads of GIP and the potential for transmission of parasitic diseases.